2014
DOI: 10.1179/1743132814y.0000000373
|View full text |Cite
|
Sign up to set email alerts
|

Straight from the horse's mouth: neurological injury in equestrian sports

Abstract: ObjectivesEquestrian sports can result in a variety of injuries to the nervous system due to many factors. We describe our series of 80 patients with injuries sustained during participation in equestrian sports.Methods and ResultsAll patients seen at the regional trauma center with injuries associated with equestrian sports between 2003 and 2011 were reviewed; 80 patients were identified. Fifty-four per cent were female and the average age was 37 years (2·2–79·3). The mean injury severity score (ISS) was 9·9 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…In the research of Srinivasan, Pierre, Plog, Srinivasan, Petraglia, Huang (2014) the percentage of women who suffered neurological injury associated with equestrian sport is higher and equal to 54%, with younger women being more at risk.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the research of Srinivasan, Pierre, Plog, Srinivasan, Petraglia, Huang (2014) the percentage of women who suffered neurological injury associated with equestrian sport is higher and equal to 54%, with younger women being more at risk.…”
Section: Discussionmentioning
confidence: 98%
“…Often the primary reason for falling from a horse is that the horse was afraid or was surprised and reacted in a way that caused injury to the rider (Srinivasan, Pierre, Plog, Srinivasan, Petraglia, Huang, 2014). Riders must always remain aware of the animal's unpredictable nature.…”
Section: Discussionmentioning
confidence: 99%
“…23 Equestrian athletes are at substantial risk of a concussion due to falls or being bucked from a horse. 27,43 Rates of concussion range from 10 to 45% of all equestrian-related injuries. 22,27,38,43,50 These estimates are conservative as rates of concussion in equestrian sports are likely underreported.…”
Section: Introductionmentioning
confidence: 99%
“…27,43 Rates of concussion range from 10 to 45% of all equestrian-related injuries. 22,27,38,43,50 These estimates are conservative as rates of concussion in equestrian sports are likely underreported. 14,27 Typically, individuals experience symptom resolution within 10 – 14 days post-concussion; 32 however 10 – 30% of individuals report persistent symptoms beyond this time frame.…”
Section: Introductionmentioning
confidence: 99%
“… 1–5 While studies have reported that head injuries account for between 13% and 48% of equestrian-related injuries, 6–11 injuries to the chest or back have been reported in 11%–54% of equestrian cases. 5–12 …”
Section: Introductionmentioning
confidence: 99%